2008
DOI: 10.1158/0008-5472.can-07-1246
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Genistein Inhibits Metastasis of Human Prostate Cancer in Mice

Abstract: Dietary genistein has been linked to lower prostate cancer (PCa) mortality. Metastasis is the ultimate cause of death from PCa. Cell detachment and invasion represent early steps in the metastatic cascade. We had shown that genistein inhibits PCa cell detachment and cell invasion in vitro. Genistein-mediated inhibition of activation of focal adhesion kinase (FAK) and of the p38 mitogen-activated protein kinase (MAPK)-heat shock protein 27 (HSP27) pathway has been shown by us to regulate PCa cell detachment and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
147
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(161 citation statements)
references
References 50 publications
(76 reference statements)
5
147
1
Order By: Relevance
“…In fact there was a trend towards tumor sensitization by the reduction in clonogenic cells recovered from unirradiated and irradiated mice with prolonged treatment with genistein. This is consistent with other reports that genistein has shown potential as an anti-cancer agent in several different cancer cell types such as glioma [181], prostate cancer [150], lung cancer [182], cervical cancer [183] and breast cancer [149]. Our results contribute to evidence that even as an anti-oxidant genistein may be used safely as a protective agent for normal tissue in combination with radiation therapy.…”
Section: Control Dietsupporting
confidence: 93%
See 1 more Smart Citation
“…In fact there was a trend towards tumor sensitization by the reduction in clonogenic cells recovered from unirradiated and irradiated mice with prolonged treatment with genistein. This is consistent with other reports that genistein has shown potential as an anti-cancer agent in several different cancer cell types such as glioma [181], prostate cancer [150], lung cancer [182], cervical cancer [183] and breast cancer [149]. Our results contribute to evidence that even as an anti-oxidant genistein may be used safely as a protective agent for normal tissue in combination with radiation therapy.…”
Section: Control Dietsupporting
confidence: 93%
“…Diets high in soy isoflavones have been noted for their role in reducing the incidence of breast and prostate cancers [147,148]. Genistein inhibits carcinogenesis in many tumour models through the modulation of genes for cell cycle, survival and apoptosis [139,146] and has been reported to reduce development of metastasis in breast cancer and prostate models [149][150][151].…”
Section: Protection Against Radiation-induced Lung Damage By Genisteinmentioning
confidence: 99%
“…In the human population, direct connections between endocrine disruptors (EDs) and prostate cancer risk have not been established. Nonetheless, due to the hormonal basis of this disease and the evidence that dietary compounds high in isoflavones (e.g., red clover, genistein) can control prostate cancer growth in humans (Jarred et al 2002, Lakshman et al 2008) and animal models (McCormick et al 2007), there is reasonable cause to evaluate and understand any potential relationship between environmental EDs and prostate cancer risk. In addition to epidemiologic studies, there are in vitro studies with human prostate cells and in vivo studies in animal models that indicate associations between EDs and prostate cancer, carcinogenesis, and/or susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Shao et al revealed that genistein exerted multiple suppressive effects on human breast carcinoma cells (21). Lakshman et al indicated that dietary genistein could inhibit metastasis of human prostate cancer (22). It has received wide attention by its potential healthbeneficial effects in the last few years (23).…”
Section: Discussionmentioning
confidence: 99%